Optimierung des didaktischen Prozesses und Streben nach Subjektivität. „Offener” Geist - Iżbińska, Katarzyna (Glottodidactica, 2005)
The following article discusses the optimization of the didactic process by using some relevant elements and by simultaneous aiming at subjectivity. Moreover, the new role of the teacher, who also becomes the mentor of his students, contributes to the improvement of this didactic process. The author of this article claims that the whole pedagogical process is the system of multiple elements which stay in mutual correlation. Not taking under consideration, explained in the article, components or isolating them from each other may lead to disturbances in functioning of the system or even its collapse which means the destruction of the didactic interaction.